Respuesta :

The matrix expressions are:

  • [tex]\left[\begin{array}{cc}12&7\\5&3\end{array}\right] * \left[\begin{array}{cc}-15&-17\\26&29\end{array}\right] = \left[\begin{array}{cc}2&-1\\3&2\end{array}\right][/tex]
  • Matrix 2 cannot be solved
  • [tex]\left[\begin{array}{cc}-2&3\\-4&5\end{array}\right] * \left[\begin{array}{c}3&4\end{array}\right] = \left[\begin{array}{c}6&8\end{array}\right][/tex]

How to solve the matrix expression?

The rule for matrix product states that:

If the dimensions of matrix A is m by n, and the dimension of matrix B is n by p.

Then, the dimension of the product matrix is: m by p

Using the above rule, we have:

Expression 1:

[tex]\left[\begin{array}{cc}12&7\\5&3\end{array}\right] * \left[\begin{array}{cc}a&b\\c&d\end{array}\right] = \left[\begin{array}{cc}2&-1\\3&2\end{array}\right][/tex]

Expand:

[tex]\left[\begin{array}{cc}12a + 7c&12b + 7d\\5a + 3c &5b + 3d\end{array}\right] = \left[\begin{array}{cc}2&-1\\3&2\end{array}\right][/tex]

By comparison, we have:

12a + 7c = 2

5a + 3c = 3

12b+ 7d = -1

5b + 3d = 2

Using a graphing tool, we have:

a = -15, b = -17, c = 26 and d = 29

Hence, the matrix expression is:

[tex]\left[\begin{array}{cc}12&7\\5&3\end{array}\right] * \left[\begin{array}{cc}-15&-17\\26&29\end{array}\right] = \left[\begin{array}{cc}2&-1\\3&2\end{array}\right][/tex]

Expression 2:

[tex]\left[\begin{array}{cc}6.75&3\\-9&-4\end{array}\right] * \left[\begin{array}{c}a&b\end{array}\right] = \left[\begin{array}{c}8&5\end{array}\right][/tex]

Expand:

[tex]\left[\begin{array}{c}6.75a +3b\\-9a - 4b\end{array}\right] = \left[\begin{array}{c}8&5\end{array}\right][/tex]

By comparison, we have:

6.75a + 3b = 8

-9a - 4b = 5

Using a graphing tool, the system of equation has no solution

Hence, the matrix expression cannot be solved

Expression 3:

[tex]\left[\begin{array}{cc}-2&3\\-4&5\end{array}\right] * \left[\begin{array}{c}a&b\end{array}\right] = \left[\begin{array}{c}6&8\end{array}\right][/tex]

Expand:

[tex]\left[\begin{array}{c}-2a +3b &-4a +5b\end{array}\right] = \left[\begin{array}{c}6&8\end{array}\right][/tex]

By comparison, we have:

-2a + 3b = 6

3a + 5b = 8

Using a graphing tool,

a = 3 and b = 4

Hence, the matrix expression is:

[tex]\left[\begin{array}{cc}-2&3\\-4&5\end{array}\right] * \left[\begin{array}{c}3&4\end{array}\right] = \left[\begin{array}{c}6&8\end{array}\right][/tex]

Read more about matrix at:

https://brainly.com/question/1821869

#SPJ1

ACCESS MORE